Analisis Variabel Akuntansi Kuartalan, Variabel Pasar, dan Arus Kas Operasi yang Mempengaruhi Bid-Ask Spread - Tumirin Tumirin (Jurnal Akuntansi dan Auditing Indonesia, 2005)
The objectives of the research are to analyze the information content of quarterly accounting variable, market variable, and operation cash flow toward bid-ask spread as well as to analyze the differences of information content between accounting variable in the fourth quarter and interim quarter in affecting bid-ask spread around the announcement of financial statement. This research uses event study method to know the effect of asset growth, asset size, leverage, liquidities, earnings variability, closing price, volume, and cash low from operation ratio on bid-ask spread. This research uses 684 samples that are 521 interim quarter and 163 fourth quarterly financial statements and concludes that the accounting variable in the announcement of quarterly finan¬cial statement which significantly affects bid-ask spread is liquidity. While the market vari¬able that significantly affects bid-ask spread are closing price and volume. All the result are consistent in the announcement of quarterly financial statement as well as in the fourth quarterly financial statement. Chow Test shows that there is no different coefficient between interim quarterly and the fourth quarterly.Keywords:    Bid-ask spread, quarterly financial statement, accounting variable, market variable, and cash flow from operation.